Synthesis and Characterization of Sago Starch Esters and Their Blends with Poly (Vinyl Chloride) - See, Yaw Koon (2007)
Esterifying of palm oil based oleochemicals like hexanoyl, octanoyl and lauroyl chloride onto dried sago starch by using formic acid as an initiator had been studied in the absence of an organic solvent. A stream of nitrogen gas had been used to eliminate the hydrochloric acid produced by the reaction. The optimum conditions in esterifying of starch hexanoate, starch octanoate and starch lauroate had been studied based on the highest percentage of the recuperation yield. About 89% of starch hexanoate, 86% of starch octanoate and 80% of starch lauraote were obtained under optimized conditions with the degree of substitution (DS) of 1.3, 1.2 and 1.2 respectively. Esterification was evidenced by the presence of ester carbonyl peak in Fourier transform infrared (FT-IR) and 1H nuclear magnetic resonance (1H-NMR). The ester group was found to act like an internal plasticizer because of the reduction of hydrogen bonds between the starch molecules. The DS of starch esters was determined by elemental analysis. The TGA had shown that the prepared starch esters had higher thermal stability than native starch and increased with the increasing of side-chain length and DS. The DSC thermograms of esterified sago starch showed the depression of glass transition temperature (Tg) from shorter side-chain length starch ester (starch hexanoate, 85 oC) to longer side-chain length starch ester (starch lauroate, 36 oC).The mechanical properties of starch esters were determined. Starch lauroate with the longest side chain length had measurable tensile strength (11.6 ± 0.5 MPa) and elongation at break (2.4 ± 0.3 %) properties compared to starch hexanoate, starch octanoate and native starch. Tensile strength and elongation at break depended on the side-chain length and the DS. Starch hexanoate, starch octanoate and starch lauroate were blended with poly(vinly chloride) (PVC) at various proportions by using conventional solventcasting technique. The FT-IR analysis showed that there were no intermolecular interactions between starch esters and PVC in room temperature. Thermal and mechanical properties, water absorption and biodegradation were investigated as a function of blend composition. The existence of starch esters had enhanced the thermal properties of PVC and increased with the increasing of starch ester content. For all blends, the mechanical properties (tensile strength and elongation at break) retained satisfactory up to 20 wt % for starch ester content. The higher the content of starch esters was the greater the decreased of mechanical properties. The blends had shown a minimal water uptake (< 4 wt %) even at the highest starch ester content (70%). The extent of their biodegradability, after exposure to sludge, was assessed by weight loss measurements. It was found that the blends were biodegradable, and the biodegradation rate decreased with increasing DS.